Comparison of Patients and their Care in Urban and Rural Specialised Palliative Home Care - A Single Service Analysis - Heckel, Maria; Stiel, Stephanie; Frauendorf, Tobias; Hanke, R. M.; Ostgathe, Christoph (Gesundheitswesen, 2016)
Specialised outpatient palliative care teams (in Germany called SAPV) aim to ensure best possible end-of-life care for outpatients with complex needs. Information on the influence of living areas (rural vs. urban) on patient and care related aspects is rare. This study aims to explore differences between palliative care patients in urban and rural dwellings concerning their nursing and service characteristics.A retrospective data analysis of documentary data for 502 patients supplied by SAPV team from December 2009 to June 2012 was conducted. Patients and care characteristics were investigated by frequency analysis and were compared for both groups of urban and rural dwelling patients (T test, Chi², Fisher's exact test p < 0.05).387 complete data sets could be included. Urban (n=197) and rural (n=190) dwelling patients were almost equally sized groups. The mean age of the whole sample was 74.5 years, 55.3% were female. Most patients were diagnosed with cancer (76.8%). No significant differences in urban and rural dwelling patients concerning most demographics, care, disease and service related aspects of palliative home care could be detected. An exception is that the rate of re-admittance to hospital is higher for rural dwelling patients (Fisher's exact test p=0.022).Although predominantly presumed, the single service analysis shows - except for the re-admittance rate to hospital - no considerable differences between palliative care patients regarding their living area. Our findings indicate that patients cared for in rural and urban settings have similar needs and impose similar requirements on palliative care teams.
EVALuna2:26206